Emerging circular bioeconomy business models - consumer products from agricultural waste: cases from Kenya and India - Gebrezgabher, Solomie A.; Odero, J.; Muthuswamy, S.; Malviya, T.; Taron, Avinandan (CGIAR Initiative on Nature-Positive Solutions, 2022)
Agricultural waste represents untapped resources that can be used to produce large value added products with many potential industrial applications. The use of agricultural wastes as raw materials for various industrial applications can help to reduce production cost and contribute to environmental conservation. The business cases described in this report highlight innovative approaches to convert the growing amount of agricultural waste into eco-efficient and bio-based products which are essential components of Nature-based solutions.